Structural and gas adsorption properties of cation exchanged zeolites - Lim, Kai Shin; Kamarudin, Khairul Sozana Nor; Chieng, Yu Yuan; Hamdan, Halimaton; Mat, Hanapi (Universiti Teknologi Petronas, 2004)
Zeolite containing silica-alumina and positively charges metal ions has the ability to adsorb molecules selectively, depending upon the size of the pore window. This is due to the arrangement of structural unit in zeolite framework that results in the generation of pores and cavities of various dimensions. However, structural properties of zeolites can be altered in a controlled manner by several modification methods. Pore modification by cation exchange method is selected to replace sodium in zeolite structural framework with other metal ions. Cationic variants of zeolite Y (LiY, MgY, BaY, AgY, and NiY) were prepared via aqueous cation exchange. Their structural properties were characterized using X-ray powder diffraction and nitrogen adsorption measurement. It was found that the presence of cation affects the structural properties of zeolite and gas adsorption characteristics. Magnesium- exchanged zeolite Y showed the strongest affinity towards methane. Sample NiY has the highest adsorption capacity for carbon dioxide.